To simplify the equation \( 2(x−5)=9−3x+6+8+3x+7 \):
Left Side:
- Use the Distributive Property on \( 2(x - 5) \): \[ 2(x - 5) = 2x - 10 \]
Response area for the left side: \( 2x - 10 \)
Right Side:
- Combine like terms on the right side: \[ 9 - 3x + 6 + 8 + 3x + 7 \] Combine the constant terms: \[ 9 + 6 + 8 + 7 = 30 \] Combine the \( -3x \) and \( 3x \): \[ -3x + 3x = 0 \] Therefore, the right side simplifies to: \[ 30 \]
Response area for the right side: \( 30 \)
Thus, the simplified equation becomes: \[ 2x - 10 = 30 \]